Management Of Student Hotspot Networks Through The Integration Of Academic Information Systems - Iqbal, Muhammad; Hariono, Tholib (NEWTON: Networking and Information Technology, 2024)
In the digital era, fast, stable, and easily accessible internet has become an essential need, particularly in academic settings. Students require reliable connectivity to support teaching and learning activities, research, and access to academic information. However, managing hotspot networks on campus often faces challenges such as user authentication, bandwidth management, monitoring, and security. To address these issues, integrating hotspot network management with Academic Information Systems (AIS) presents a potential solution. This integration allows the hotspot network system to utilize academic data for authentication and authorization, enhancing efficiency, security, and ease of access. Case studies at several universities have shown significant improvements in operational efficiency and user satisfaction following the implementation of this integration. This research aims to develop a hotspot network management system integrated with AIS to support a more modern and integrated educational ecosystem and enhance the quality of internet access services on campus.